Sensor-Aided Localized Capsule-Cooling Using Neural Networks for Energy-Efficient Refrigeration - N. Banerjee; P. K. Sadhu; N. Pal; R. Swaroop (Journal of Engineering Science and Technology Review, 2014)
Sensor-aided localized capsule-cooling technique is a unique refrigeration process where sensors precisely capsulate the location of an item(s) on a shelf of a fridge and hence direct the governing artificial intelligence to take suitable action. Here the sensors are used to locate the objects and the designed smart system (neural network) activates the corresponding ductlines to cool the object. Here neural network system opens the gate(s) and tilts the angle to allow the flow of cool air through the ductlines. Then the orifices, which fall in the virtual “Hot Region”, the domain that the active sensors had created almost immediately on sensing an obstruction, are opened. The orifices and sensors are arranged in a series on the lower wall of the ductlines to allow flow of air in the downward direction. These open orifices facilitate the direct hitting of cool air on the target-item and hence create a cold block within a fridge, instead of cooling the entire fridge uniformly, to keep the singular item refrigerated. This mode of operation offering selective cooling, rather than the conventional uniform one, is useful in saving energy, as the region then needed to be cooled is reduced significantly. A detail structural and theoretical explanations along with graphical analysis clearly elucidate the effective working of this mechanism under practical circumstances is given here. In this paper neural network is used for capsule cooling for energy efficient refrigeration